2019
DOI: 10.1038/s41550-019-0757-4
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evidence for co-condensed oxygen- and carbon-rich meteoritic stardust from nova outbursts

Abstract: Although their parent stars no longer exist, the isotopic and chemical compositions and microstructure of individual stardust grains identified in meteorites provide unique constraints on dust formation and thermodynamical conditions in stellar outflows 1-4. Novae are stellar explosions that take place in the hydrogen-rich envelope accreted onto the surface of a white dwarf in a close binary system 5. The energy released by a suite of nuclear processes operating in the envelope 2 powers a thermonuclear runaway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…To date, more than 1500 O‐rich presolar grains have been identified with stellar origins including RGB, AGB stars, novae, and SNe (e.g., Bose et al., 2010, 2012, 2014; Busemann et al., 2009; Choi et al., 1998, 1999; Davidson et al., 2012, 2014, 2015; Ebata et al., 2006; Floss et al., 2006, 2010, 2013; Floss & Stadermann, 2009a, 2009b, 2012; Gyngard, Nittler, et al., 2010; Gyngard, Zinner, et al., 2010; Haenecour et al., 2013, 2018, 2019, 2020; Huss et al., 1994; Keller & Messenger, 2011; Leitner et al., 2012, 2014, 2016, 2020; Messenger et al., 2003, 2005; Mostefaoui & Hoppe, 2004; Nagashima et al., 2004; Nguyen & Messenger, 2014; Nguyen et al., 2007, 2010; Nguyen & Zinner, 2004; Nittler et al., 1994, 1997, 1998, 2008, 2018; Tonotani et al., 2006; Vollmer et al., 2009; Zhao et al., 2010, 2011, 2013; Zinner et al., 2003, 2005). Of the grains identified in meteorites, only ~10% are attributed to origins in the ejecta of SNe (Haenecour et al., 2018), though as previously mentioned, recent nucleosynthetic modeling suggests this fraction could be much higher, as some Group 1 and Group 2 presolar silicate grains could originate in SNe (Hoppe et al., 2021; Leitner & Hoppe, 2019; Verdier‐Paoletti et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, more than 1500 O‐rich presolar grains have been identified with stellar origins including RGB, AGB stars, novae, and SNe (e.g., Bose et al., 2010, 2012, 2014; Busemann et al., 2009; Choi et al., 1998, 1999; Davidson et al., 2012, 2014, 2015; Ebata et al., 2006; Floss et al., 2006, 2010, 2013; Floss & Stadermann, 2009a, 2009b, 2012; Gyngard, Nittler, et al., 2010; Gyngard, Zinner, et al., 2010; Haenecour et al., 2013, 2018, 2019, 2020; Huss et al., 1994; Keller & Messenger, 2011; Leitner et al., 2012, 2014, 2016, 2020; Messenger et al., 2003, 2005; Mostefaoui & Hoppe, 2004; Nagashima et al., 2004; Nguyen & Messenger, 2014; Nguyen et al., 2007, 2010; Nguyen & Zinner, 2004; Nittler et al., 1994, 1997, 1998, 2008, 2018; Tonotani et al., 2006; Vollmer et al., 2009; Zhao et al., 2010, 2011, 2013; Zinner et al., 2003, 2005). Of the grains identified in meteorites, only ~10% are attributed to origins in the ejecta of SNe (Haenecour et al., 2018), though as previously mentioned, recent nucleosynthetic modeling suggests this fraction could be much higher, as some Group 1 and Group 2 presolar silicate grains could originate in SNe (Hoppe et al., 2021; Leitner & Hoppe, 2019; Verdier‐Paoletti et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Electron transparent cross sections (<100 nm in projected thickness) of the selected grains were prepared for detailed structural and chemical analyses using the Thermo Fisher Scientific (formerly FEI) Helios G 3 focused ion beam scanning electron microscope (FIB-SEM) located in the Kuiper Materials Imaging and Characterization Facility (KMICF) at the Lunar and Planetary Laboratory (LPL), University of Arizona. The procedure for producing electron transparent cross sections of presolar grains was described in many papers (Haenecour et al, 2019(Haenecour et al, , 2020Holzapfel et al, 2009;Leitner et al, 2012Leitner et al, , 2016Nguyen et al, 2007Nguyen et al, , 2016Stroud et al, 2004;Vollmer et al, 2007Vollmer et al, , 2009Vollmer et al, , 2013Zega et al, 2007Zega et al, , 2011Zega et al, , 2014Zega et al, , 2015Zega et al, , 2020. Briefly, we first go through an alignment procedure to ensure that we capture the anomalous region of interest, initially identified with NanoSIMS, in our FIB transect.…”
Section: Samples and Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electron transparent (<100 nm in projected thickness) cross-sections of four grains were prepared using the Thermo Fisher Scientific (formerly FEI) Helios G 3 focused-ion beam scanning-electron microscope (FIB-SEM) located in the Kuiper Materials Imaging and Characterization Facility (KMICF) at the Lunar and Planetary Laboratory (LPL), University of Arizona. The general procedure for producing electron transparent cross-sections of presolar grains is described in several previous papers (e.g., Haenecour et al, 2019Haenecour et al, , 2020Holzapfel et al, 2009;Seifert et al, 2022c;Zega et al, 2007Zega et al, , 2011Zega et al, , 2014bZega et al, , 2015Zega et al, , 2020. Briefly, we first go through an alignment procedure, described in detail in Seifert et al (2022c) to ensure that we capture the presolar grain identified in the NanoSIMS with our FIB transect.…”
Section: Sample and Experimental Methodsmentioning
confidence: 99%
“…Electron-transparent sections (<100 nm in projected thickness) of five grains, three from MET 00526 and two from QUE 97008 and three matrix sections were prepared using the Thermo Fisher Scientific (formerly FEI) Helios G 3 focused ion beam-scanning electron microscope (FIB-SEM) located in the Kuiper Materials Imaging and Characterization Facility (KMICF) at the Lunar and Planetary Laboratory (LPL), University of Arizona. We followed previously described procedures for producing electron-transparent cross sections of presolar grains, which is described in detail in the literature (Haenecour et al, 2019(Haenecour et al, , 2020Holzapfel et al, 2009;Leitner et al, 2012Leitner et al, , 2016Nguyen et al, 2007Nguyen et al, , 2016Seifert et al, 2022Seifert et al, , 2023Stroud et al, 2004;Vollmer et al, 2007Vollmer et al, , 2009Vollmer et al, , 2013Zega et al, 2007Zega et al, , 2011Zega et al, , 2014Zega et al, , 2015Zega et al, , 2020.…”
Section: Samples and Methodsmentioning
confidence: 99%